THE fertilization, pruning and controlled fires on the growth of Feijoa sellowiana (O. Berg) O. Berg. - Gurski, Elivelton; Melo Hoffmann, Pablo; Cesar Furlaneto Sampaio, André; Thomas Blum , Christopher; Bergmann Carlucci, Marcos; Camargo Angelo, Alessandro; Borgo, Marília; Velazco, Santiago José Elías (Comunicata Scientiae, 2023)
Feijoa sellowiana (O.Berg) O. Berg is an ornamental and food plant, as well as an important species for ecological restoration and landscaping that still requires much research before consolidating it in the tropical market. To understand if the implementation of techniques focusing on improving fruit production at its wild condition would affect the species’ development, we planted 216 saplings of various mother trees in an incomplete factorial block design applied in nine treatments. We tested formative aerial pruning (drastic intensity), fertilization (chemical and organic), and the effect of controlled fires prior to planting. We evaluated biomass alterations by systematically measuring the third sapling of each treatment, quantifying fresh and dry matter in two periods. We also measured changes in height (H), root collar diameter (RCD), and the H/RCD ratio. We carried out nine measurements during 27 months and used linear mixed-effects models to consolidate the long-term evaluation. Our results indicate a positive effect from the organic fertilization on the plants’ height, a momentary increase in RCD caused by programmed fires, and an increase in the H/RCD ratio due to formative aerial pruning (increasing resistance). Fertilization did not accelerate the increase in RCD and had no effect on the H/RCD ratio.